Follow‐up study of skin cancer in a U.K. paediatric transplant population. (3rd December 2018) - Foo, S.H.; Nightingale, P.G.; Gazzani, P.; Bader, E.; Ogboli, M.; Martin‐Clavijo, A.; Milford, D.V.; Kelly, D.A.; Moss, C.; Thomson, M.A.
Summary: It is well‐known that adults who undergo liver or kidney transplantation are more likely to develop skin cancer. This is because medicines given to prevent rejection of the transplanted organ also lower the body's resistance to cancer. Less is known about the skin cancer risk in children who have undergone organ transplantation (paediatric organ transplant recipients, POTRs). In this study, researchers in Birmingham, U.K. examined 45 patients for skin cancer following liver or kidney transplantation in childhood. The same patients had been examined 10 years earlier, when no skin cancers were found. Their average age was now 24 years, and time since transplantation ranged from 15 to 26 years. Ethnically, 34 were white, while 7 had racially pigmented skin. Again, there were no skin cancers or suspicious lesions, but 41 of the 45 had significantly more moles than 10 years earlier, 71% in sun‐exposed sites, particularly arms. Eleven had more than 50 moles, an excessively high number indicating an increased risk of melanoma skin cancer. Despite previous advice about sun‐protection because of the skin cancer risk, 78% had experienced sunburn, particularly those who took holidays abroad, and 22% admitted using sunbeds. Those who had been sunburnt more often had more moles on the legs and back. Curiously those with more moles on the arms had used more sunscreen, but perhaps not enough for their amount of sun exposure. The lack of skin cancer in these POTRs at 15‐26 years post‐transplant is encouraging and compares well with other studies showing first cancers in POTRs at 12‐19 years. However, it is no cause for complacency: these young people remain at risk and clearly need better, age‐appropriate education about sun‐protection. Abstract : Linked Article: Foo et al. Br J Dermatol 2018;179 :1368–1375